Resistance Training Prevents Deterioration in Quadriceps Muscle Function During Acute Exacerbations of Chronic Obstructive Pulmonary Disease - Troosters, Thierry; Probst, Vanessa Suziane; Crul, Tim; Pitta, Fabio; Gayan-Ramirez, Ghislaine; Decramer, Marc; Gosselink, Rik (American journal of respiratory and critical care medicine, 2010)
Exacerbations of chronic obstructive pulmonary disease (COPD) acutely reduce skeletal muscle strength and result in long-term loss of functional capacity. To investigate whether resistance training is feasible and safe and can prevent deteriorating muscle function during exacerbations of COPD. Forty patients (FEV(1) 49 +/- 17% predicted) hospitalized with a severe COPD exacerbation were randomized to receive usual care or an additional resistance training program during the hospital admission. Patients were followed up for 1 month after discharge. Primary outcomes were quadriceps force and systemic inflammation. A muscle biopsy was taken in a subgroup of patients to assess anabolic and catabolic pathways. Resistance training did not yield higher systemic inflammation as indicated by C-reactive protein levels and could be completed uneventfully. Enhanced quadriceps force was seen at discharge (+9.7 +/- 16% in the training group; -1 +/- 13% in control subjects; P = 0.05) and at 1 month follow-up in the patients who trained. The 6-minute walking distance improved after discharge only in the group who received resistance training (median 34; interquartile range, 14-61 m; P = 0.002). In a subgroup of patients a muscle biopsy showed a more anabolic status of skeletal muscle in patients who followed training. Myostatin was lower (P = 0.03) and the myogenin/MyoD ratio tended to be higher (P = 0.08) in the training group compared with control subjects. Resistance training is safe, successfully counteracts skeletal muscle dysfunction during acute exacerbations of COPD, and may up-regulate the anabolic milieu in the skeletal muscle. Clinical trial registered with www.clinicaltrials.gov (NCT00877084).